Management and Outcome After Multivisceral Resections in Patients with Locally Advanced Primary Colon Cancer. Issue 4 (April 2018) - Rosander, Emma; Nordenvall, Caroline; Sjövall, Annika; Hjern, Fredrik; Holm, Torbjörn
Abstract : BACKGROUND: Locally advanced colon cancer invading surrounding organs or structures is challenging to surgeons and oncologists. Multivisceral resections with tumor removal en bloc with invaded tissues provide the best chance for cure. OBJECTIVE: We aimed to assess the management and outcomes after multivisceral resections in patients with clinically infiltrative, locally advanced primary colon cancer. DESIGN: This is a descriptive retrospective cohort study. SETTINGS: A total of 121 consecutive patients with locally advanced primary colon cancer underwent en bloc multivisceral resections at a tertiary referral unit for colorectal cancer between 2007 and 2014. MAIN OUTCOME MEASURES: Patient demographics, surgical details, histopathological findings, and outcomes were analyzed through registry data and reviews of patient files. RESULTS: An R0 resection was achieved in 112 patients (92.6%), and an R1 resection was achieved in 9 patients (7.4%). Actual tumor cell infiltration in resected tissues was found in 77 patients (63.6%), and inflammation was found in 44 patients (36.4%). The estimated 5-year overall survival was 60.8% and 86.9%. Survival was significantly better after R0 than after R1 resections. After a median follow-up of 28 months, recurrent disease was diagnosed in 25 patients (20.7%). Female sex, low tumor stage, and adjuvant chemotherapy, but not tumor infiltration per se, were independently associated with better overall survival in a multivariate analysis. LIMITATIONS: The main limitations of the study are the retrospective design and the fact that all patients were operated on at 1 institution by a small number of surgeons. CONCLUSIONS: Patients with locally advanced colon cancer can be cured with an R0 resection. All involved surrounding tissues should be removed en bloc with the primary tumor. SeeVideo Abstract athttp://links.lww.com/DCR/A548 .